Control of the frequency response of a narrow-band filter for the X-band frequency based on a photonic crystal with a movable cylindrical defect - E. A. Ryabov; A. A. Andreev; S. A. Sergeev; A. I. Mikhailov (Российский технологический журнал, 2025)
Objectives. The work set out to investigate the possibility and effectivity of using a movable cylindrical defect with metal pins in the design of a photonic crystal to control the frequency response of a narrow-band filter in a rectangular waveguide having a cross-section of 23 × 10 mm in the X-band, as well as to determine the most effective methods for controlling frequency response.Methods. A numerical simulation of the frequency response of the filter was carried out using the openEMS software package, which is based on Maxwell’s equations solved by the finite-difference time-domain method. The frequency response of the currently proposed and implemented filter construction in the X-band was further investigated in an experimental study.Results. Numerical simulation shows that a resonant transmission peak in the stopband of the frequency response can be caused to appear by introducing a movable cylindrical defect having two metal pins into the center of a photonic crystal structure. In addition, the position of this peak on the frequency response can be effectively controlled by rotating the cylindrical defect around its axis. If the position of the defect remains unchanged, an increase in the frequency of the transmission peak occurs as a result of decreasing the period of the photonic crystal. However, the frequency of this resonant transmission peak is most strongly influenced by changes in the size of holes in the photonic structure. These changes can be used to control both the position and shape of the transmission peak, as well as the overall frequency response. At the same time, the difference in transmission remains practically unchanged when the cylinder rotates around its axis. The simulation results were confirmed by the data of an experimental study of the frequency response of photonic crystals made from PETG plastic using 3D printing technology.Conclusions. The proposed, designed, and manufactured experimental samples of narrow-band filters in the X-band based on a photonic crystal demonstrated reliably variable transmission values and the possibility of controlling the resonant peak frequency and thus the entire frequency response, including operational control. This makes them very promising for practical use in radio-electronic equipment.